Modelling respiration rate of soybean seeds (Glycine max (L.)) in hermetic storage - Ochandio, D. (2017)
The dynamic of oxygen (O2) and carbon dioxide (CO2) concentration was characterized in soybean (Glycine max (L.)) samples hermetically stored in glass jars at 15, 25 and 35 °C and 13, 15 and 17% moisture content (m.c., wet base). Two correlations were used for smoothing gas concentration in time: linear and exponential. Then, the respiration rate at each temperature and m.c. combination was calculated as storage time progressed and oxygen was consumed and two predictive models for respiration were proposed: Model I (temperature and m.c. dependent) and Model II (temperature, m.c. and oxygen dependent). It was observed that respiration rate increased with storage m.c. and temperature. However, respiration rate was not mainly affected by O2 until a critical concentration limit of about 2% was reached. Respiration rates were from 0.341 to 22.684 mg O2/(kgDM d) and from 0.130 to 20.272 mg CO2/(kgDM d) for a range of storage condition of 13–17% m.c. and 15–35 °C temperature. The respiration rate of soybean seeds obtained in this study resulted significantly lower than the rates reported in the literature for other grains at similar temperature and aw (water activity) storage condition. For hermetic storage simulations in which O2 concentration is not expected to drop below 2%, the simplest model (Model I) could be used, but if the O2 concentration of the hermetic system is expected to be depleted, Model I would under estimate the time at which O2 is consumed, and thus a model with O2 dependency is recommended instead (Model II).